Sistem Monitoring Pengolahan Limbah di Rumah Sakit Berbasis IOT - Jessica Morenly Panigoro; Dhea Intan Pandjaitan; Marson James Biduman (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
Hospital is a health service institution that generates a lot of waste. Management and handling of hospital waste is currently a concern. A waste water treatment system is needed in a hospital so that when it is released into the environment it does not have an impact on the environment. Wastewater Treatment Plant (WWTP) is one solution to overcome the problem of environmental pollution, with the construction of installations Wastewater Treatment can reduce environmental pollution problems especially the problem of wastewater. Domestic wastewater pollution at this time if there is no proper action to deal with it, it will cause serious problems. To solve this problem, wastewater needs to undergo a treatment process before flowing into the aquatic system. And it is also possible that a lot of waste treatment is done manually with the occasional checking method and manual filtering. So it is necessary to do the selection of waste water management technology is therefore very important. To manage this waste, it is planned to use a waste water reservoir with anaerobic-aerobic biofilter media.